A prospective interventional study of recombinant human interleukin-11 mouthwash in chemotherapy-induced oral mucositis - Hangping Wei; Juan Wei; Xiaofang Dong (BMC, 2022)
Abstract Background This prospective interventional study aimed to evaluate and analyse the efficacy of rhIL-11 mouthwash compared to Kangfuxin fluid in treatment and blank control in prevention of oral mucositis (OM) in patients receiving chemotherapy. Materials and Methods In total, 50 patients in the treatment group and 62 patients in the prevention group were included. Subsequently, each group was divided into an experimental group and a control group. In the treatment group, the experimental patients received recombinant human interleukin-11 (rhIL-11) mouthwash, whereas the control group received Kangfuxin fluid. In the prevention group, experimental patients still received rhIL-11 mouthwash based on routine oral care, whereas the control group only received routine oral care. Meanwhile, we observed and recorded the efficacy in the treatment group, and the occurrence and grades of OM in the prevention group. Results Through statistical analysis, the results showed that on the seventh day of treatment, the experimental group showed more improvement compared to the control group, and it was statistically significant (p = 0.032). The average healing time in the experimental group (3.59 ± 1.927 days) was shorter than that in the control group (4.96 ± 2.421 days; p = 0.031). In the prevention group, we observed the incidence of oral mucositis. No significant differences were found in the occurrence and grades of OM in the experimental and control groups (p = 0.175). Conclusion Our preliminary results indicate that rhIL-11 mouthwash may be a superior option to treat OM, especially in severe cases, compared to Kangfuxin fluid. However, there is no advantage in prevention.